Application of CHAID Algorithm for the Identification of Morphological Traits of Indigenous Sheep Body Weight: Significant traits of body weight by CHAID Analysis. - Arsalan, Muhammad; Aman Ullah, Muhammad; Waheed, Abdul (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The objective of this research study was the identification of significant morphological traits to predict the live body weight of indigenous sheep of southern Punjab, Pakistan. Application of Chi-Square Automatic Interaction Detection (CHAID) was used to achieve the objective of the current study. Pearson correlation technique was used to see the relationship of morphological traits with live body weight. The data of 13 morphological traits of 291 indigenous sheep was used using a simple random sample technique. The morphological traits such as barrel depth, body length, ear length, ear width, head length, head width, heart girth, neck length, neck width, rump length, rump width, tail length, and withers height were used. The data consists of 130 rams and 161 eves. The dependent variable was the live body weight of indigenous sheep. The barrel depth, rump width, and heart girth were strongly correlated with live bodyweight having correlations 0.968, 0.936, and 0.925 respectively. The result of CHAID analysis showed that barrel depth and heart girth are significant predictors of live body weight (p-value<0.001).